Cybersecurity regulation: cybersecurity certification of operational technologies - Tsvilii, Olena (Technology audit and production reserves, 2021)
The object of research is the system and schemes of conformity assessment (certification) of cybersecurity of operational technologies (OT), as a set of rules and procedures that describe the objects of certification, determine the specified requirements and provide a methodology for certification. The terminological base and conceptual apparatus of the study of cybersecurity certification of operational technologies are based on the international standard ISO 17000:2020 Conformity assessment – Vocabulary and general principles. Cybersecurity certification systems and schemes are based on assessment standards, the choice and application of which is not unambiguous and historically has many interpretations and application mechanisms. These standards consist of tools, policies, security concepts, security assurances, guidelines, risk management approaches, best practices, safeguards, and technologies. But they have, to one degree or another, a significant drawback – the complexity of transforming the results of information security assessment according to these standards into security guarantees with any wide international recognition. In the context of globalization, this significantly degrades the cybersecurity quality. The main hypothesis of research is that the cybersecurity quality can be improved by converging towards a common methodology that is based on agreed international standards and international best practice for certification. The question of the key role of cybersecurity for operational technologies, which become the basis for Economy 4.0 and are now considered as a new frontier of cybersecurity, is considered. The need to create a system and schemes for certification of OT cybersecurity based on international and European certification principles is shown. A hierarchical model of cybersecurity certification system assessment standards and a hierarchical model of agreements on mutual recognition of cybersecurity certificates have been developed, which will allow a systematic approach to the creation of a system and schemes for OT cybersecurity certification. This provides an opportunity for developers of systems and certification schemes to form OT cybersecurity certification systems based on the principles of wide cross-border recognition of OT cybersecurity certificates.